2014
DOI: 10.1590/0004-2730000003116
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive pituitary lesion with a remarkably high Ki-67

Abstract: SUMMARYThe uncommon aggressive pituitary tumors are named carcinomas when metastases are detected, either in the central nervous system and/or systemically. Some cases are associated with hormonal overproduction, but most are diagnosed because of local symptoms. These neoplasias are generally refractory to current treatments. A 51 year-old woman presented sudden onset of headache, left arm paresis and left facial hypoesthesia. Computed tomography scan and magnetic resonance imaging revealed a pituitary tumor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…These data suggest a possible involvement of ADAM12L in the cell proliferation of pituitary adenomas. ADAM12L might play this role by shedding HB‐EGF, thereby enhancing the EGFR‐dependent signaling pathway …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest a possible involvement of ADAM12L in the cell proliferation of pituitary adenomas. ADAM12L might play this role by shedding HB‐EGF, thereby enhancing the EGFR‐dependent signaling pathway …”
Section: Discussionmentioning
confidence: 99%
“…There is controversy in the literature, as considerable variations in Ki-67 immunolabelling (MIB-1 index) of pituitary adenomas have been reported. 36,37 Most researchers found that Ki-67 immunoreactivity was associated with tumor invasiveness in pituitary adenomas and could serve as a prognostic biomarker 36,[38][39][40][41] ; only a few authors drew the opposite conclusions. 42,43 In our study, a significantly higher MIB-1 index was observed in invasive adenomas versus noninvasive pituitary adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein Ki-67 is a cell proliferation marker detected by the monoclonal antibody MIB-1 and is expressed as a percentage of immunopositive nuclei in the form of a Ki-67 proliferation index [ 5 ]. According to Thapar et al Ki-67 over 3% is a criterion to distinguish invasive from noninvasive adenomas with 97% specificity and 73% sensitivity [ 5 , 6 ]. In this case, after 3 years, the adenoma progressed to a carcinoma, as evidenced by p53 expression and diffuse Ki-67 staining.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, pituitary carcinomas develop craniospinal, lung, liver, and ovary metastases. Immunohistochemical staining of these metastases reveals elevated rates of oncoproteins such as p53 and cell proliferation marker (Ki-67), which is helpful for diagnosis and prognostic relevance in these cases [ 4 , 6 ]. It is worth noting that the levels of those markers are typically higher in metastases than in the primary tumor [ 6 ].…”
Section: Discussionmentioning
confidence: 99%